Effect of Gas Type and Its Pressure on Nanobubble Generation - Bunkin, Nikolai F.; Shkirin, Alexey V.; Penkov, Nikita V.; Goltayev, Mikhail V.; Ignatiev, Pavel S.; Gudkov, Sergey V.; Izmailov, Andrey Yu. (Frontiers in Chemistry, 2021)
The dependence of the volume number density of ion-stabilized gas nanobubbles (bubstons) on the type of gas and the pressure created by this gas in deionized water and saline solution has been investigated. The range of external pressures from the saturated water vapor (17 Torr) to 5 atm was studied. It turned out that the growth rate of the volume number density of bubstons is controlled by the magnitude of the molecular polarizability of dissolved gases. The highest densities of bubstons were obtained for gases whose molecules have a dipole moment. At fixed external pressure and the polarizability of gas molecules, the addition of external ions leads to a sharp increase in the content of bubstons.